THE GROWTH AND LIPID EXTRACTION FROM FRESH WATER MICROALGAE - SCENEDESMUS QUADRICAUDA - NGUYEN, TIEN THANH (2015)
Recently, microalgae becomes a promising feedstock for biofuel, specially for biodiesel, due to their fast growing and high lipid content. The present study was conducted in order to investigate the effect of different culture mediums, air injection rates, nitrogen concentrations, and CO2 concentrations by using a flat plate and a column photobioreactor on growth rate, cell biomass concentration, and composition of cell biomass of Scenedesmus quadricauda. The result about the effect of different medium shows that, from column photobioreactor, BG-11 medium resulted in higher growth rate, cell biomass concentration and lipid content than Lefebvre-Czarda medium. The result about the effect of air injection rate shows that, at low air injection rate range, from both the photobioreactors, growth rate and cell biomass concentration were enhanced significantly by the increase of air injection rate.